Designing novel antibacterials: application of omics science - Zaman, Aubhishek M.; Razzaque, Samsad (© 2013 AVES Ibrahim Kara, 2016)
This article was published in Klimik Dergisi [ © 2013 Klimik Dergisi ] and the definite version is available at : http://doi.org/10.5152/kd.2013.02. The Journal's website is at: http://klimikdergisi.org/eng/makale/943/83/Full-Text